FINANCIAL DISTRESS AND PROFITABILITY OF TIER THREE COMMERCIAL BANKS IN KENYA - Kimathi, Caroline M.; Mungai, Dr. John (American Journal of Finance, 2018)
Purpose: This study is aimed at analysing the effect of financial distress on the profitability of tier three commercial banks in Kenya. Methodology: Financial distress was proxied using non-performing loans, leverage and liquidity. Profitability was indicated using return on assets ratio. The study sampled twenty commercial banks and used casual research design. The study estimated a multiple regression linear model. Results: The study established that non-performing loans have a negative and statistically significant effect, Leverage had a positive and statistically significant effect while Liquidity had a positive and statistically insignificant effect on the profitability of tier three commercial banks in Kenya.